The indulgences for the Cathedral of Huesca, an example for the study of the edition of incunable Bulls - de los Reyes Gómez, Fermín; Pedraza Gracia, Manuel José (Revista General de Información y Documentación, 2019)
The exceptional conservation of copies of a bull of indulgences for the Cathedral of Huesca provides a better understanding of the process of printing and publishing these documents, which were frequent during the Incunabula period. The need to produce simultaneous copies of bulls for the living and for the dead, together with the existence of a single engraving for the first one, made it necessary to produce various compositions that are the subject of an interesting analysis of material bibliography.